DHE in the Pharmacotherapy of Migraine: Potential for a Larger Role - Saper, Joel R.; Silberstein, Stephen; Dodick, David; Rapoport, Alan (Headache, 2006)
Despite a large array of currently marketed, frequently effective drugs for the acute treatment of migraine headache, comprising various classes and formulations, predictably reliable treatment for most headache types is often lacking. Dihydroergotamine mesylate (DHE) is a comparatively safe and effective therapy for migraine headache that could potentially be used for a broader range of headache types than occurs at present. The features of DHE supporting this assertion include (1) effectiveness in terminating severe, long‐lasting headaches, (2) rapid onset of action, (3) very low rates of headache recurrence, (4) minimal risk of medication‐overuse headache, and (5) in the nasal spray formulation, suitability for outpatients (especially patients who are very nauseated or vomiting, potentially obviating the need for an office or hospital visit for acute care). Conditions or circumstances for which there are data supporting the expanded use of DHE include menstrual migraine, migraine with central sensitization and cutaneous allodynia, medication‐overuse headache, migraine recurrence, and status migrainosus. The introduction of the intranasal formulation of DHE provides both pharmacologic and patient‐convenience advantages for use in migraine therapy. This article reviews the rationale for the use of DHE in these common, often difficult‐to‐treat migraine forms.